2020
DOI: 10.1002/cbin.11481
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole overcomes paclitaxel‐resistance and enhances anticancer effects of paclitaxel by inducing autophagy in A549/Taxol cells

Abstract: Non‐small‐cell lung cancer (NSCLC) is one of the most common malignancies, and the occurrence of drug‐resistance severely limits the efficacy of anticancer drugs in the treatment of NSCLC. Identification of new agents to reverse drug‐resistance in NSCLC treatment is of great importance and urgency both clinically and scientifically. In the present study, we found that A549/Taxol cells displayed a high level of resistance to paclitaxel with the resistance index up to 231. Importantly, esomeprazole could potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Today, there is a great controversy about the role of autophagy in the death and survival of tumor cells. Although some research assures that autophagy is one of the mechanisms of antitumor agents, such as Taxol ® , for killing cancer cells, others suggest that it is a cell survival mechanism [ 124 , 125 , 126 , 127 ]. Therefore, it is necessary to continue conducting research to clarify how autophagy influences the development of cancer and to develop new therapeutic treatments [ 128 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is a great controversy about the role of autophagy in the death and survival of tumor cells. Although some research assures that autophagy is one of the mechanisms of antitumor agents, such as Taxol ® , for killing cancer cells, others suggest that it is a cell survival mechanism [ 124 , 125 , 126 , 127 ]. Therefore, it is necessary to continue conducting research to clarify how autophagy influences the development of cancer and to develop new therapeutic treatments [ 128 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that only the gene expressions of PGP were induced might be due to the fact that PGP was the most predominant transporter coping with xenobiotics in A549 cells. [ 40 ] The activities of MRPs detected in this experiment could be partially caused by PGP, due to their overlapping substrate/inhibitor specificities. [ 41,42 ] These results also explained the more effective effects of VAL in enhancing the cellular toxicity of each chemical (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multidrug resistance is a great challenge for paclitaxel to exert effect on cancers (Wang et al, 2018a). While, it was found that esomeprazole could overcome drug resistance of paclitaxel and enhance its anticancer effects by inducing autophagy in A549/Taxol cells (Bai et al, 2021). In a randomized phase II preoperative study, combination of autophagy inhibitor hydroxychloroquine and gemcitabine and nab-paclitaxel could exert autophagy inhibition in pancreatic cancer patients (Zeh et al, 2020) (Figure 2A).…”
Section: Paclitaxelmentioning
confidence: 99%